2016
DOI: 10.1177/1753425916647471
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of CCL11: genetic characterization in lagomorphs and evidence of positive and purifying selection in mammals

Abstract: The interactions between chemokines and their receptors are crucial for differentiation and activation of inflammatory cells. CC chemokine ligand 11 (CCL11) binds to CCR3 and to CCR5 that in leporids underwent gene conversion with CCR2. Here, we genetically characterized CCL11 in lagomorphs (leporids and pikas). All lagomorphs have a potentially functional CCL11, and the Pygmy rabbit has a mutation in the stop codon that leads to a longer protein. Other mammals also have mutations at the stop codon that result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Our outcomes reveal that several sites in other proteins, which are under substantial positive selection have been developing more swiftly than the mature protein [43][44][45]. As a result, the dynamic selection forces its change which concerns to improve the protein secretion efficacy, which is true in case of PD-L2 protein ( Figure 3C), which is unlike than the matured protein [46,47].…”
Section: Agingmentioning
confidence: 89%
“…Our outcomes reveal that several sites in other proteins, which are under substantial positive selection have been developing more swiftly than the mature protein [43][44][45]. As a result, the dynamic selection forces its change which concerns to improve the protein secretion efficacy, which is true in case of PD-L2 protein ( Figure 3C), which is unlike than the matured protein [46,47].…”
Section: Agingmentioning
confidence: 89%
“…Virtual transcripts of Lepus and Ochotona TRIM5 PRYSPRY domains were created by splicing together the exons reads (~ 600 bp) and have been deposited in the GenBank database under the following accession numbers: #MN605824 ( Ochotona hoffmanni ), #MN605825 ( Ochotona hyperborean) , #MN605826 ( Ochotona mantchurica ), #MN605827 ( Ochotona pallasi ), #MN605828 ( Ochotona rutila ), #MN605829 ( Ochotona turuchanensis ), #MN605830 ( Ochotona alpina ), #MN605831 ( Ochotona pusilla ), #MN605832 ( Ochotona dauurica ), #MN605833 ( Lepus capensis ), #MN605834 ( Lepus castroviejoi ), #MN605835 ( Lepus corsicanus ), #MN605836 ( Lepus timidus ), #MN605837 ( Lepus townsendii ), #MN605838 ( Lepus americanus ), #MN605839 ( Lepus californicus ). Lepus and Ochotona samples have been used in previous publications [4952]…”
Section: Methodsmentioning
confidence: 99%
“…The remaining samples were available in the CIBIO tissue samples collection. Approval from an ethics committee was unnecessary since no animals were killed for the purpose of this study and these samples have been described and used in previous publications [15, 19, 22, 3941]. Total RNA was extracted from liver tissue of one specimen of American pika by using the RNeasy Mini Kit (Qiagen, Hilden, Germany) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The study of CCL8 , a prime ligand of CCR5, revealed that this gene was pseudogenized only in those species that underwent the CCR5 alteration, while it remained intact in hares and Eastern cottontail ( S. floridanus ) [16, 17]. In contrast, CCL3, CCL4, CCL5 and CCL11 genes were found to be functional in all studied leporids [18, 19]. While in rabbit, mouse and rat CCL3 and CCL4 are encoded by a single functional gene, they are duplicated in other rodents such as squirrel and guinea pig, being either functional or inactivated [20, 21].…”
Section: Introductionmentioning
confidence: 99%